Virality, Justice and the Principle of “Blocking the Means to Evil” - Tanzilulloh, M. Ilham; Agmar, Khoirun Nisa Aprilian (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Social media virality can expedite the resolution of legal cases, but it is not a suitable foundation for attaining genuine justice in Indonesian law enforcement because it can lead to inequality and human rights violations, particularly when viewed through the lens of Islamic law, which places a strong emphasis on preventing injustice. This research explains how the virality of social media affects the existence of a just legal construction from the perspective of Islamic law. Combining juridical and empirical approaches, this research draws on primary data from viral cases in several journal articles, analysed using the normative-qualitative method. Legal materials used to analyse data include primary legal materials, such as laws and regulations, secondary legal materials in textbooks containing legal theories and reasoning, and journals. The research results are presented in descriptive-analytical form. The results of this study reveal that although viral legal cases receive faster attention, the phenomenon of